Keigo learning in building omotenashi no kokoro through a communicative language teaching approach - Sari, Christine Dian Permata; Kastuti, Teti Indriati (Japanese Research on Linguistics, Literature, and Culture, 2023)
In building interpersonal relationships through omotenashi no kokoro (Excellent Service), Keigo is a crucial aspect to consider when communicating in Japanese. Keigo, both in terms of grammar and its usage concept, is quite complicated. Therefore, the role of instructors in delivering Keigo learning materials is expected to motivate students to improve their communication skills while mastering the art of creating interpersonal connections. Communicative Language Teaching (CLT) is chosen as the teaching method. This research aims to provide an alternative teaching experience focusing on omotenashi no kokoro. The research method used is descriptive with a qualitative approach. The research subjects are students of the Japanese Language Program at Universitas Teknologi Yogyakarta (UTY) taking the hospitality course. The research is conducted through observation by analyzing CLT-based learning activities using three steps: mechanical practice, meaningful practice, and communicative practice. The study results indicate that with the CLT method, students can use Keigo through word or phrase repetition, understand the meaning of words and expressions in sentences, and freely actualize themselves through improvisation and exploration of conversational contexts. A new finding from this research is that the CLT teaching method is effective when applied to the hospitality course, emphasizing building interpersonal relationships through omotenashi no kokoro.